Child poverty in Malaysia: what do Malaysians think? - Jamaiudin, Norhaslinda; Mahmud, Maziah (UiTM, 2023)
Multidimensionality of child poverty discloses the complexity of poverty across a range of aspects. Children are vulnerable to many unfortunate possibilities that include material and social deprivation. In this context, most children faced insufficient monetary resources, limited access to food, education and quality healthcare. This eventually would lead to the long-term damage on children’s opportunities and development. The dynamics of child poverty therefore have driven many governments to establish appropriate measures in addressing the needs of children in poverty. Unfortunately, in Malaysia the issue of child poverty has not received the policy attention it deserves. Current measures of battling poverty are usually directed to poor households with little attention devoted to the needs of children specifically due to the fact that they were not classified as a separate group for policy consideration. As a result, there has been insignificant allocation of funds for the improvement of children’s well-being. To provide sufficient insights on the issue of child poverty, the study examines the policy problem from public perspective. Policy debates over how best to help poor children in Malaysia have prompted the study to assess public perception on adequacy of policy measures and forms of deprivation faced by children living in poor households. The findings reveal that children are deprived materially and socially. School dropouts (92.1%), lack of electronic devices for online learning (87.3 %), lack of attention from parents due to the need for overtime work (86.5 %), growth problem (79.7%) and the lack of nutritious food (87.2 %) are strongly perceived to be associated to child deprivation. Given its importance, majority of the respondents believed that bold and decisive actions are pivotal to construct more salient policies for fighting child poverty in Malaysia.